Analisis Sikap Tanggung Jawab dalam Pelaksanaan Program Merdeka Belajar di Masa Pandemi Covid-19 Pada Siswa SD - Debby Pratiwi; Fitroh Setyo Putro Pribowo; Fajar Setiawan (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2021)
This study aims to describe the analysis of the attitude of responsibility in the implementation of the independent learning program during the COVID-19 pandemic in elementary school students. The research method used in this study is a descriptive qualitative approach with data collection in the form of observations, interviews, and anecdotal notes. The result of this research is that 52.5% of 40 students have achieved all indicators of responsibility. Responsibility is self-awareness in carrying out duties and obligations without coercion. Online learning is an implementation of independent learning that has been carried out since the covid-19 pandemic. During online learning students carry out their responsibilities in the form of doing assignments given by the teacher, students even have the responsibility to help parents 47.5% of students who do not carry out their full responsibilities during online learning due to several factors, namely: boredom, poor internet network. not good, and the work piled up. Responsible students have good time management by setting priorities. Students who have a responsible attitude are accustomed to learning independently during online learning. The role of the family and the surrounding environment is needed by students in the implementation of online learning. This role can be in the form of mentoring while studying to guide students if they have difficulty doing their assignments. Schools and teachers should reduce assignments that burden students.